2020
DOI: 10.1038/s41598-020-59624-w
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated nano-graphene oxide as a nanocarrier for delivering mixed anticancer drugs to improve anticancer activity

Abstract: Due to their high specific surface area, graphene oxide and graphene oxide-base nanoparticles have great potential both in dual-drug delivery and combination chemotherapy. Herein, we developed cisplatin (pt) and doxorubicin (DoX) dual-drug-loaded peGylated nano-graphene oxide (pGo) to facilitate combined chemotherapy in one system. In this study, nano-sized pGO-Pt/DOX ranged around 161.50 nm was fabricated and characterized using zeta-potential, AFM, TEM, Raman, UV-Vis, and FTIR analyses. The drug delivery eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(105 citation statements)
references
References 66 publications
3
101
1
Order By: Relevance
“…Pei et al demonstrated the co-delivery of two drugs, cisplatin (Pt), combined with DOX using four-armed PEG-functionalized NGO for enhanced synergistic therapeutic effect [ 139 ]. The synthesis first involves the preparation of PEGylated GO.…”
Section: Graphene Oxide Nanoparticles: Synthesis Unique Propertiementioning
confidence: 99%
See 1 more Smart Citation
“…Pei et al demonstrated the co-delivery of two drugs, cisplatin (Pt), combined with DOX using four-armed PEG-functionalized NGO for enhanced synergistic therapeutic effect [ 139 ]. The synthesis first involves the preparation of PEGylated GO.…”
Section: Graphene Oxide Nanoparticles: Synthesis Unique Propertiementioning
confidence: 99%
“…The drug release behavior was studied at two different pH values. At pH 7.4, Pt and DOX’s release was 28.4% and 29.1%, respectively, over 72 h. At pH 5.3, the amount of Pt and DOX released was 30% and 41%, respectively, in the first 4 h, which increased to 65.7% and 64.6%, respectively, in 72 h [ 139 ].…”
Section: Graphene Oxide Nanoparticles: Synthesis Unique Propertiementioning
confidence: 99%
“…51 Recently, Pei et al developed cisplatin and doxorubicin dual-drug-loaded PEGylated nano-graphene oxide which exhibited significantly increased anticancer effect than the single drug delivery system. 52 Wang et al synthesized folate-modified GO/ PEI siRNA nanocomplexes which successfully targeted ovarian cancer cells in vitro. 53 Shirvalilou et al developed magnetic NGO as a drug carrier for improving gliomatargeted iodo-2-deoxyuridine (IUdR) delivery and imaging.…”
Section: Dovepressmentioning
confidence: 99%
“…They found that GO inhibits cell division and the formation of cell spheres through epigenetic mechanisms responsible for cell differentiation, reducing their ability to proliferate. Pei et al [ 31 ] proved that GO nanoparticles are not toxic to cells, but the addition of PEGylated nano-graphene oxide to cisplatin (Pt) and doxorubicin (DOX) anticancer drugs resulted in apoptosis and necrosis of cancer cells, but also in a reduction in tumor size in vivo.…”
Section: Introductionmentioning
confidence: 99%